Diagnostic utility of amyloid PET in cerebral amyloid angiopathy-related symptomatic intracerebral hemorrhage - Baron, Jean-Claude (Nature Publishing Group, 2014)
By detecting β-amyloid (Aβ) in the wall of cortical arterioles, amyloid positron emission tomography (PET) imaging might help diagnose cerebral amyloid angiopathy (CAA) in patients with lobar intracerebral hemorrhage (l-ICH). No previous study has directly assessed the diagnostic value of (11)C-Pittsburgh compound B (PiB) PET in probable CAA-related l-ICH against healthy controls (HCs). (11)C-PiB-PET and magnetic resonance imaging (MRI) including T2* were obtained in 11 nondemented patients fulfilling the Boston criteria for probable CAA-related symptomatic l-ICH (sl-ICH) and 20 HCs without cognitive complaints or impairment. After optimal spatial normalization, cerebral spinal fluid (CSF)-corrected PiB distribution volume ratios (DVRs) were obtained. There was no significant difference in whole cortex or regional DVRs between CAA patients and age-matched HCs. The whole cortex DVR was above the 95% confidence limit in 4/9 HCs and 10/11 CAA patients (sensitivity=91%, specificity=55%). Region/frontal or occipital ratios did not have better discriminative value. Similar but less accurate results were found using visual analysis. In patients with sl-ICH, (11)C-PiB-PET has low specificity for CAA due to the frequent occurrence of high (11)C-PiB uptake in the healthy elderly reflecting incipient Alzheimer's disease (AD), which might also be present in suspected CAA. However, a negative PiB scan rules out CAA with excellent sensitivity, which has clinical implications for prognostication and selection of candidates for drug trials.